Spray Deposition of n-type Cobalt-Doped CuO Thin Films: Influence of Cobalt Doping on Structural, Morphological, Electrical, and Optical Properties - Asl, Hassan Zare; Rozati, Seyed Mohammad (Journal of electronic materials, 2020)
The effects of cobalt (Co)-doping (0 at%, 2 at%, 4 at%, 6 at%, and 10 at%) on the structural, morphological, electrical, and optical characteristics of spray-deposited nanostructured copper oxide (CuO) thin films were investigated. X-ray diffraction patterns revealed that the crystallite size is subject to a constant reduction with an increase in the doping concentration. Based on field-emission scanning electron microscopy images, no change was observed for the grain shapes; however, the grain size decreased with an increase in the doping concentration. Furthermore, doping Co led to a conversion from a fairly weak p -type conductivity for the undoped CuO thin film (3.42 × 10 −4 Ω cm) to a considerable n -type conductivity for the 10 at% Co-doped CuO (CuO:Co) film (4.20 × 10 −1 Ω cm). Although the mobility of the resulting films decreased with Co doping, it seems that the significant enlargement in free electron carrier concentration is responsible for conductivity transition and improvement. Finally, the bandgap values were estimated using experimental data of transmittance and reflectance.